Functional Inhibition of Aquaporin‐3 With a Gold‐Based Compound Induces Blockage of Cell Proliferation. Issue 11 (November 2014) - Serna, Ana; Galán‐Cobo, Ana; Rodrigues, Claudia; Sánchez‐Gomar, Ismael; Toledo‐Aral, Juan José; Moura, Teresa F.; Casini, Angela; Soveral, Graça; Echevarría, Miriam
<x xml:space="preserve">Abstract</x> AQP3 has been correlated with higher transport of glycerol, increment of ATP content, and larger proliferation capacity. Recently, we described the gold(III) complex Auphen as a very selective and potent inhibitor of AQP3's glycerol permeability (Pgly). Here we evaluated Auphen effect on the proliferation of various mammalian cell lines differing in AQP3 expression level: no expression (PC12), moderate (NIH/3T3) or high (A431) endogenous expression, cells stably expressing AQP3 (PC12‐AQP3), and human HEK293T cells transiently transfected (HEK‐AQP3) for AQP3 expression. Proliferation was evaluated in the absence or presence of Auphen (5 μM) by counting number of viable cells and analyzing 5‐bromo‐2′‐deoxyuridine (BrdU) incorporation. Auphen reduced ≈50% the proliferation in A431 and PC12‐AQP3, ≈15% in HEK‐AQP3 and had no effect in PC12‐wt and NIH/3T3. Strong arrest in the S‐G2/M phases of the cell cycle, supported by analysis of cyclins (A, B1, D1, E) levels, was observed in AQP3‐expressing cells treated with Auphen. Flow‐cytometry of propidium iodide incorporation and measurements of mitochondrial dehydrogenases activity confirmed absence of cytotoxic effect of the drug. Functional studies evidenced ≈50% inhibition of A431 Pgly by Auphen, showing that the compound's antiproliferative effect correlates with its ability to inhibit AQP3 Pgly. Role of Cys‐40 on AQP3 permeability blockage by Auphen was confirmed by analyzing the mutated protein (AQP3‐Ser‐40). Accordingly, cells transfected with mutated AQP3 gained resistance to the antiproliferative effect of Auphen. These results highlight an Auphen inhibitory effect on proliferation of cells expressing AQP3 and suggest a targeted therapeutic effect on carcinomas with large AQP3 expression. J. Cell. Physiol. 229: 1787–1801, 2014. © 2014 Wiley Periodicals, Inc.